Prevalence, predictors and clinical significance of Blastocystis sp. in Sebha, Libya - Abdulsalam, A.M.; Ithoi, I.; Al-Mekhlafi, H.M.; Khan, A.H.; Ahmed, A.; Surin, Johari; Mak, J.W. (BMC, 2013)
Blastocystis sp. has a worldwide distribution and is often the most common human intestinal protozoan reported in children and adults in developing countries. The clinical relevance of Blastocystis sp. remains controversial. This study was undertaken to determine the prevalence of Blastocystis infection and its association with gastrointestinal symptoms among outpatients in Sebha city, Libya.